Pre-Marital Education (PME) Program Through Online Media to Improve Behavior on Stunting Prevention - Huriah, Titih; Suci, Rovi Apriani Eka; Puspita, Dewi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Stunting is a condition that affects toddlers who are shorter than their age. Stunting in Yogyakarta was most prevalent in Gunungkidul Regency (17.94%) and least prevalent in Bantul Regency (7.73%). Tepus sub-district is one of the Gunungkidul Regency sub-districts with the highest prevalence of stunting. One of the efforts to reduce stunting prevalence is educational intervention related to the first 1000 days of life. Late adolescents or early adults planning to marry may be the target of interventions in the first 1000 days of life to improve stunting prevention behaviours. This study aimed to determine the effectiveness of the Pre-Marital Education program for increasing stunting prevention behaviour. This study uses a quantitative method (Quasy Experiment). The sample in this study was 19 pairs in the intervention group and the control group. The instruments used in the research are questionnaires in the form of google forms, and educational media used posters and videos. Pre-Marital Education uses Instagram's online media. The data analysis in this study used the Wilcoxon Signed Rank Test and Mann-Whitney Test. The results showed that the behaviour in the intervention group had signed with a p-value = 0,000, while the control group was not significant with a p-value of more than 0,05. The Mann-Whitney U test analysis results in both groups after the intervention were 0,002 with a p-value of less than 0,05, which means that Pre-Marital Education affects the behaviour of pre-marital couples in preventing stunting. Pre-Marital Education effectively increases stunting prevention behaviour in pre-marital couples. Abstrak: Stunting merupakan keadaan balita yang mempunyai tinggi badan yang kurang dibandingkan balita seusianya. Prevalensi stunting tertinggi di Yogyakarta adalah Kabupaten Gunungkidul 17,94% dan terendah di Kabupaten Bantul 7,73%. Kecamatan Tepus merupakan salah satu kecamatan di Kabupaten Gunungkidul dengan angka prevalensi stunting paling tinggi. Salah satu upaya menurunkan prevelensi stunting yaitu intervensi edukasi terkait 1000 hari pertama kehidupan. Remaja akhir atau dewasa awal yang merencanakan pernikahan dapat menjadi sasaran intervensi 1000 hari pertama kehidupan untuk meningkatkan perilaku pencegahan stunting. Tujuan penelitian ini untuk mengetahui bagaimana efektivitas program Pre-Marital Education untuk peningkatan perilaku pencegahan stunting. Penelitian ini menggunakan metode kuantitatif (Quasy Eksperimen). Sample pada penelitian ini berjumlah 19 pasangan pada kelompok intervensi maupun kelompok kontrol. Pre-Marital Education ini menggunakan media online Instagram. Hasil penelitian menunjukan bahwa perilaku pada kelompok intervensi memiliki signifikansi dengan nilai p= 0,000, sedangkan kelompok kontrol tidak signifikan dengan nilai p lebih dari 0,05. Hasil analisis Mann Whitney U Test pada kedua kelompok setelah intervensi hasilnya 0,002 dengan nilai p kurang dari 0,05 yang artinya terdapat pengaruh Pre-Marital Education terhadap perilaku pasangan pranikah dalam pencegahan stunting. Kesimpulan Pre-Marital Education efektif untuk peningkatan perilaku pencegahan stunting pada pasangan pranikah.